Perspectives on Arabic Linguistics : Papers from the Annual Symposium on Arabic Linguistics. Volume VIII: Amherst, Massachusetts 1994. - Eid, Mushira (John Benjamins Pub. Co., 1996)
This volume includes ten papers selected from the Eighth Annual Symposium on Arabic Linguistics, held at the University of Massachusetts, Amherst, 1994. Six of them deal with the syntax of Arabic two with phonology, and two with variation. The topics represented in the volume include binding in Arabic, the analysis of negation and negative polarity items, pronoun doubling in codeswitching, linguistic variation and language change, voice assimilation in Arabic dialects, among others. The volume includes contributions by the following: Mahasen Abu Mansour; Maher Bahloul; Raja Bahloul; Elabbas Benm.